COMPENSATION SYSTEMS AND CAREER DEVELOPMENT AS DETERMINANTS OF WORK MOTIVATION IN POLICE ORGANIZATIONS - Rahmadsyah Lubis; Benyamin Lufpi (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Compensation systems and career development are central human resource levers that influence work motivation within police organizations. This literature review synthesizes empirical and conceptual studies published between 2015 and 2025 to examine how monetary and non monetary compensation, promotion policies, career pathways, and professional development opportunities determine motivation among police personnel. The review employs a structured literature search across academic databases, followed by qualitative synthesis of twenty five peer reviewed articles and institutional reports. Findings indicate that compensation fairness and transparency, alignment of rewards with performance, and clear merit based promotion systems enhance extrinsic motivation while career development initiatives foster intrinsic motivation, professional identity, and long term retention. Career development that includes mentorship, competency frameworks, and continuous training strengthens affective commitment which amplifies motivational effects from compensation. Contextual moderators such as organizational culture, budgetary constraints, unionization, and national employment norms shape the magnitude of these relationships. Notable tensions appear when compensation policies prioritize seniority over competency, creating misalignment between motivational incentives and desired behavioral outcomes. The review highlights methodological gaps including limited longitudinal studies, inconsistent operationalization of motivation, and scarce research on combined effects of compensation systems and career development in police settings. Practical implications emphasize integrated HR strategies that balance equitable compensation with transparent career development mechanisms to sustain motivation and organizational performance. The article concludes with a research agenda calling for longitudinal mixed method studies, cross jurisdictional comparisons, and experimental evaluations of incentive structures in policing contexts.